The Dynamics of Emotional and Ethical Interactions: Rethinking Subjectivity in Posthuman Conditions (Prithvi Journal of Research and Innovation, 2025)
This paper examines the subjectivity of clones in Kazuo Ishiguro’s Never Let Me Go (2005) and dispensables in Ninni Holmqvist’s The Unit (2008) in posthuman conditions. Despite their social exclusion, the protagonists in both novels demonstrate their relational and ethical capacities as forms of defiance. The paper particularly analyzes how Kathy, Ishiguro’s protagonist, and Dorrit, Holmqvist’s equivalent, resist the social systems that deny their full human status and affirm their selfhood through their emotional ties and moral responsiveness. While navigating societies that reduce them to expendables or biological objects, both protagonists employ relational and moral engagements as strategies to challenge their dehumanization. Previous scholarship has largely investigated biopolitical control, commodification of bodies, and marginalization of clones and dispensables in the novels, overlooking the emotional and ethical dynamics of these characters’ lives. This paper addresses this gap, exploring the protagonists’ capacities for friendship and love, empathy and care, art and memory, and their connection to nonhuman entities within worlds that treat them as disposable bodies. It incorporates the theoretical insights of posthumanism, propounded by Braidotti, Haraway, and Barad, emphasizing the concept of relational subjectivity. Using both primary and secondary sources, the paper adopts a qualitative research design and a critical analysis method. The findings of this paper highlight that subjectivity emerges not only from biological or social status but also from affective and creative capacities, and shared vulnerability, thereby reconceptualizing the expendables as emergent posthumans.